2016
DOI: 10.5530/ijper.50.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polymer Based Mucoadhesive Hydrogel Beads of Nizatidine: Preparation, Characterization and Evaluation.

Abstract: Background: Dosage forms which precisely control the release rates and targets drugs to a specific body site have made enormous impact in the formulation and development of novel drug delivery systems. Methods: A prolonged release mucoadhesive hydrogel system of nizatidine was prepared by ionotropic gelation and polyelectrolyte complexation technique using natural, biodegradable polymers with or without chitosan. Prepared formulations were subjected to in vitro evaluation and several characterization studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 11 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Despite alginate, chitosan exhibits remarkable adhesive properties. Hydrogels composed of chitosan-alginate, which act as a coating for a drug core, as reported by Patil et al (2016) , display superior mucoadhesive characteristics compared to dressings without chitosan [ 54 , 75 ]. However, pure chitosan is not appropriate for cell attachment studies due to its cationic nature.…”
Section: Assessments Of Hydrogels Properties For Wound Dressings Prop...mentioning
confidence: 99%
“…Despite alginate, chitosan exhibits remarkable adhesive properties. Hydrogels composed of chitosan-alginate, which act as a coating for a drug core, as reported by Patil et al (2016) , display superior mucoadhesive characteristics compared to dressings without chitosan [ 54 , 75 ]. However, pure chitosan is not appropriate for cell attachment studies due to its cationic nature.…”
Section: Assessments Of Hydrogels Properties For Wound Dressings Prop...mentioning
confidence: 99%
“…It was reported that the formation of hydrogels using Alg and Ch can be achieved by adjusting the pH of the mixing solution without adding calcium cations [12,13]. Patil et al proved that hydrogel based on Ch-Alg formulations had a higher mucoadhesive strength compared to hydrogel based on Alg [14]. In addition, Ch molecular weight in Ch-Alg polyelectrolyte complex film containing clindamycin phosphate affected to adhesiveness of complex films [15].…”
Section: Introductionmentioning
confidence: 99%
“…microcarrier(Zakiah et al, 2015) (Sathali and Varun, 2012). The swelling of CMC-microcarriers was governed by the degree of crosslinking, with greater cross-linkages reducing the swelling due to limited space available for the diffusion of free water into the polymer network (CheNan et al, 2019;Patil et al, 2016;Tuan Mohamood et al, 2021). Lower S w was found in samples with higher gel content percentages (CMC-3, CMC-6, and CMC-9), while S w value rose in samples with low gel content (CMC-1, CMC-4, and CMC-7).…”
mentioning
confidence: 99%